Síntese de novos aza-heterociclos possuindo núcleos pirimidínicos e triazinônicos com potencial aplicação sintética - Gonçalves, Davana Silva (2015)
The obtaining of the new and versatile pyrimidine polyfunctionalized (79%) was possible from the cyclocondensation reaction of β-enaminodicetone [EtCO2C(O)C(=CHNMe2)C(O)CO2Et] with benzamidine hydrochloride. The reactivity of the pyrimidine polyfunctionalized obtained was tested front the 1,2-dinucleophiles hydrazine monohydrate, phenylhydrazine and 4-chlorophenylhydrazine, leading to attainment of heterocycles 5-carboxyethyl-2-phenylpyrimido[4,5-d]pyridazin-8(7H)-one (83%), 5-carboxyethyl-2,7-difenilpirimido[4,5-d]pyridazin-8-one (83%) and 5-carboxyethyl-7-(4-chlorophenyl)-2-phenylpyrimido[4,5-d]pyridazin-8-one (67%). Moreover, the reaction of the pyrimidine polyfunctionalized with hydroxylamine hydrochloride to obtain the new heterocyclic 5-carboxyethyl-2-phenylpyrimido[4,5-d][1,2] oxazin-8-one (70%), and was possibility of isolating its intermediate 4-carboxyethyl-5- (2-ethoxy-1-hydroxyimino-2-oxoacetyl)-2-phenylpyrimidine (86%). The reactivity of pyrimidine polyfunctionalized was also tested against 1,4-dinucleophile 1,2-phenylenediamine, leading to obtaining heterocyclic 3-(4-carboxyethyl-2-phenyl-pyrimidin-5-yl)quinoxalin-2(1H)-one (60%). Also, it obtained the synthesis of N-carbo-hydrazide derivative (51-62%) from the compound pyrimido[4,5-d]pyridazin-8-ones. And, from the N-carbo-hydrazide derivative with substituent 4-clorohidrazina was obtained carbo-acilhydrazonic (73%), confirming the synthetic potential they have. The synthesis to obtain 6-methyl-4-(N,N-dimethylfomimidamidil)-[1,2,4](3H)triazin-5-one (79%) was made from the intramolecular cyclization of N'-[(2-(dimethylamino) methylene)hydrazinyl)-1-oxopropan-2-ylidene]-N,N-dimethylhydrazonoformamida using acid catalysis BF3.MeOH. Through a one-pot reaction of 2-hydrazonopropanohydrazida with 2 equivalents of DMFDMA or DMADMA and catalysis of acid BF3.MeOH, also was possible to obtain new 6-methyl-4-(N,N-dimethylfomimidamidil)-[1,2,4](3H)triazin-5-one (94%) and 6-methyl-4-(N,N-dimethylacetimidamidil)-[1,2,4](3H)triazin-5-one (62% )